Influence Counseling with Smart Calendar Media (Kalpin) to Knowledge and Attitude of Pregnant Women about First 1000 Days of Life (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2019)
Malnutrition in pregnant women has an impact on the health of the next generation. Therefore, nutrition counseling first 1000 days of life needs to be given. Good nutrition during the period of 1000 days starting from early pregnancy until the child’s second birthday. This study aims to determine the effect of counseling with “Kalpin” or Smart Calendar on knowledge and attitude of pregnant women about the first 1000 days of life. This type of research is a comparative analytic design with pre-test and post-test control group. Nutrition counseling activities carried out by the lecture method using a smart calendar. Measurement of knowledge and attitude of pregnant women perfomed twice: before and after the extension granted. Analysis of the data used were bivariate analysis test Independent T-Test and Mann Whitney. The result shows influence of counseling about first 1000 days of life with Kalpin to knowledge (p = 0,000) and attitude of pregnant woman (p = 0,000) about first 1000 days of life. For health service can be a new input in efforts to improve the quality of service with realization the Program Healthy Indonesia that include first 1000 days of life.